(untitled) (Fiep Bulletin - online, 2013)
Obesity is a public health problem worldwide, with an aging population began to worry about the appearance of this phenomenon in the elderly population and its consequences. We know that older people practicing regular physical activities tend to reduce body weight and thus its mass index (BMI), is preventing diseases, especially those related to obesity. The gymnastics has gained ground among the elderly. This study aimed to identify the characteristics of BMI of Older participants in a group fitness for a particular institution of Porto Alegre. Gymnastics sessions were held 2x per week lasting 1h, for 5 months. The experimental methodology was characterized by an almost experimental methodology, the kind before and after the study with only one group. Survey participants were in agreement with the resolution 196/96 of the National Health Council The sample consisted of 47 elderly above 60 years. The results showed that older adults improved BMI after the intervention of the gymnastics program. In relation to normal and overweight, both had a decrease of 4%, however malnutrition and obesity 0% 47% continued with the same percentage. From the results it was concluded that the gymnastics program influenced the decrease in BMI of the elderly.